Ovarian tissue cryopreservation and retransplantation–what do patients think about it? - Lotz, Laura; Maktabi, Amina; Hoffmann, Inge; Findeklee, Sebastian; Beckmann, Matthias; Dittrich, Ralf (Reproductive Biomedicine Online, 2016)
Cryopreservation of ovarian tissue has been successfully applied clinically, with over 60 live births to date. The aim of the present study was to perform a survey of patients who have had ovarian tissue cryopreserved in the Department of Obstetrics and Gynecology, Erlangen University Hospital, in order to obtain information about: why patients opt for fertility preservation; their current fertility; pregnancy attempts and outcomes; and their intended plans for the cryopreserved ovarian tissue. In total, 147 women took part in the survey (average age 25.0 ± 7.0 years; response rate 48%; mean follow-up period 6 years). Sixty-six reported regular menstrual cycles; 48 were amenorrhoeic. Sixty-two women had tried to conceive; 33 reported pregnancies. Twenty-five had delivered healthy children after conceiving naturally; eight had conceived with assisted reproduction. Five patients had had their ovarian tissue retransplanted. Although many patients continued to have ovarian function, none of them regretted choosing cryopreservation of ovarian tissue. Cryopreservation of ovarian tissue is an effective option and is very important for women diagnosed with cancer. Analyses of the clinical outcomes in these patients are essential in order to identify those patients capable of benefiting most from the procedure and in order to improve the technique.
EVALuna2:32986